2019
DOI: 10.1111/andr.12668
|View full text |Cite
|
Sign up to set email alerts
|

Early administration of phosphodiesterase 5 inhibitors after induction of diabetes in a rat model may prevent erectile dysfunction

Abstract: BackgroundThe possible role of phosphodiesterase 5 inhibitors (PDE5Is) in prevention of negative effect of diabetes mellitus (DM) on erectile function is not well settled.ObjectivesTo investigate the effect of early administration of vardenafil on erectile function, cavernosal structure, and genes expression in a rat model of DM.Materials and methodsThis experimental study was carried out at Suez Canal University's research laboratory. This study was conducted on a total of 60 adult male Albino Wistar rats, ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Furthermore, we analyzed cell type-specific transcriptional changes due to diabetes ( Figure 1F and Figure 1—figure supplement 2A–G ). We found that Nos3 (highly expressed in the untreated diabetes group compared to the treatment group) decreased in diabetic valve-related LEC and VEC ( Ismail et al, 2020 ). In addition, Igfbp2 and Igfbp4 (lowly expressed in the penis of diabetic rats) were also downregulated in diabetic SMCs and Chonds, respectively, whereas Igfbp3 was upregulated in diabetic FB and MFB ( Abdelbaky et al, 1998 ).…”
Section: Resultsmentioning
confidence: 78%
“…Furthermore, we analyzed cell type-specific transcriptional changes due to diabetes ( Figure 1F and Figure 1—figure supplement 2A–G ). We found that Nos3 (highly expressed in the untreated diabetes group compared to the treatment group) decreased in diabetic valve-related LEC and VEC ( Ismail et al, 2020 ). In addition, Igfbp2 and Igfbp4 (lowly expressed in the penis of diabetic rats) were also downregulated in diabetic SMCs and Chonds, respectively, whereas Igfbp3 was upregulated in diabetic FB and MFB ( Abdelbaky et al, 1998 ).…”
Section: Resultsmentioning
confidence: 78%
“…2A-G). We found that Nos3 (highly expressed in the untreated diabetes group compared to the treatment group) decreased in diabetic valve-related LEC and VEC (Ismail et al, 2020). In addition, Igfbp2 and Igfbp4 (lowly expressed in the penis of diabetic rats) were also downregulated in diabetic SMC and chondrocytes, respectively, whereas Igfbp3 was upregulated in diabetic FB and Myo-FB (Abdelbaky et al, 1998).…”
Section: Single Cell Transcriptional Landscape Of Mouse Cavernous Tissuementioning
confidence: 78%
“…We chose TGF‐beta‐1 expression for CF assessment, as this pleiotropic cytokine has been shown to induce collagen synthesis in cavernosal tissue in vitro 30,31 . Also, TGF‐beta‐1 overexpression is associated with CF occurrence in animal and human studies, making it one of the CF markers 9,32,33 . Unfortunately, it was technically impossible to conduct RT‐PCR to analyze TGF‐beta‐1 expression due to the absence of RNA in penile tissue samples that underwent micro‐CT.…”
Section: Discussionmentioning
confidence: 99%
“…30,31 Also, TGF-beta-1 overexpression is associated with CF occurrence in animal and human studies, making it one of the CF markers. 9,32,33 Unfortunately, it was technically impossible to conduct RT-PCR to analyze TGF-beta-1 expression due to the absence of RNA in penile tissue samples that underwent micro-CT. RNA disruption during micro-CT was the reason why TGF-beta-1 expression analysis could not be performed and also provoked low efficiency of DNase processing, probably due to the formation of crosslinks in the DNA, making it inaccessible to DNase. 34 The study's main aim was to compare the capabilities of micro-CT imaging and radiodensity assessment for CF evaluation in the whole penile sample with the following analysis by acknowledged methods, such as histological, histochemical, immunohistochemical, and RT-PCR evaluation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation